Inflammaging in Skin and Other Tissues - The Roles of Complement System and Macrophage - Zhuang, Yong; Lyga, John (Inflammation & Allergy-Drug Targets (Discontinued), 2014)
Inflammaging refers to a continuous, low-grade inflammation associated with aging. Such chronic inflammatory response could build up with time and gradually causes tissue damage. It is considered as one of the driving forces for many age-related diseases such as diabetes, atherosclerosis, age-related macular degeneration (AMD), and skin aging. There is mounting evidence that indicates aging is driven by the pro-inflammatory cytokines and substances produced by our body’s innate immune system. The macrophage and complement system, two important components of innate immune system, have attracted more and more attention since they appear to be involved in the pathogenesis of several inflammaging-associated diseases, such as AMD and atherosclerosis. This paper will review what we know about these two innate immune systems in the pathogenesis of AMD, atherosclerosis and skin aging.
Keywords: macrophage